Consumption of processed food & food away from home in big cities, small towns, and rural areas of Tanzania. (10th July 2021) - Sauer, Christine M.; Reardon, Thomas; Tschirley, David; Liverpool‐Tasie, Saweda; Awokuse, Titus; Alphonce, Roselyne; Ndyetabula, Daniel; Waized, Betty
Abstract: We study household consumption of various categories of processed food, including ultra‐processed food and meals away from home in Tanzania. We compare peri‐urban versus hinterland rural areas, and large cities versus small towns. Three sets of findings stand out. (1) Contrary to the common view in Africa that processed food is mainly an urban middle‐class phenomenon, we found it has penetrated the diets of the rural areas and the rural and urban poor. In rural areas, surprisingly 60% of food consumption comes from purchases in value terms, and processed food accounts for 76% of purchases and 47% of all food consumed. For the rural poor, purchased processed food is 38% of food consumption. In urban areas processed food's share of purchases (hence consumption) is 78%, similar for the rich and poor. (2) We found that ultra‐processed food (such as sugar‐sweetened beverages and cookies) and meals‐away‐from‐home (MAFH) have emerged as important in urban as well as rural areas. As these foods tend to be high in oil, salt, and sugar, this is a health concern. The share of ultra‐processed foods and MAFH is 21% in rural areas and 36% in cities albeit twice as high in large cities compared with small towns and among richer compared to poorer consumers. (3) Our regressions show the spread of processed food consumption in rural and urban areas, among the rich and poor, is driven mainly by opportunity costs of the time of women and men, and thus the pursuit of saving home‐processing and cooking time, as well as food environment factors. As these drivers are long term trends this suggests processed food consumption will continue to grow.